Penerapan Model Team Assisted Individualization Untuk Meningkatkan Hasil Belajar Siswa - Oktavianus, Randys; Baan, Anastasia; Tanduk, Rita (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The objectives of this research are (1) to describe the teacher's ability to apply the Team Assisted Individualization type cooperative learning model to improve Indonesian language learning outcomes, (2) to describe students' Indonesian language learning outcomes through the application of the Team Assisted Individualization type cooperative learning model in class VIII students at State Middle Schools. 4 South Makale. The type of research used in this research is qualitative research. The data collection techniques used in this research were observation, interviews, tests, field notes and documentation. The results of this research show that 1) the teacher's ability to manage learning using the Team Assisted Individualization type cooperative learning model for students is classified as very good. This can be seen from the overall average score of 4.57 over the three meetings; 2) student learning outcomes increase with the Team Assisted Individualization learning model. This can be seen from the results of the initial test (pre-test) of 25 students, none of whom achieved a KKM score ≥ 70 because they only got an average score of 30.90, while in the final test (post-test) only 3 people did not complete it. of 25 students with an average score of 80.35. Classically and individually, students achieve completeness of the KKM score in the final test after being given treatment compared to the initial test before being given treatment.